Control of a two-pressure distillation column. (August 2020) - Luyben, William L.
Abstract: A recent paper explored the separation of the close-boiling mixture 1, 2 propanediol (PDO) and ethylene glycol (EG). The optimum operating pressure using a traditional single vessel was 282 kPa with a reboiler duty of 399 kW. However, the vapor–liquid equilibrium shifts with pressure such that higher pressure is favorable in the PDO-rich region. An interesting steady-state design was developed that splits the column into a high-pressure rectifier (4.9 bar) and a low-pressure stripper (2.38 bar). A compressor (32 kW) moves vapor from the top of the stripper into the bottom of the rectifier. The hot vapor leaving the top of the rectifier at 244 °C provides all the heat required in the reboiler at the base of the stripper (234 °C). This novel design reduces energy cost by 85%. An effective control structure for this complex process is developed in this paper. A small auxiliary reboiler and condenser are used to stabilize the system and to handle large disturbances in throughput and feed composition. Highlights: Operating a distillation column with different pressures in the stripping and rectifying sections can drastically reduce energy costs. The vapor from the overhead of the high-pressure rectification section provides the heat required in the reboiler of the low-pressure stripping section. At design conditions the process is heat balanced, but dynamic control in the face of disturbances requires either removal or addition of auxiliary heat. A split-ranged heat-duty control structure provides effective control by manipulating both heat added in an auxiliary reboiler and heat removed in an auxiliary condenser.